'Revenge porn' and the actio iniuriarum: using 'old law' to solve 'new problems'. (5th July 2018) - Brown, Jonathan
Abstract: 'Revenge porn' is conceptualised as a modern phenomenon which the law is not equipped to deal with. The advent of smartphone technology has allowed sexually explicit material to be created easily and disseminated quickly. An increasing number of individuals have fallen victim to this phenomenon in recent years. This paper submits that victims of revenge porn ought to be held due monetary redress in the civil law, while acknowledging that the damage done by revenge porn need not necessarily involve a loss. Victims of revenge porn are likely to suffer from severe emotional distress and upset, but these injuries are non-patrimonial. This can consequently make it difficult to frame an action for damages. This paper asks if the delict iniuria might offer appropriate remedy in instances of revenge porn. The actio iniuriarum was, in Roman law, a delict which served to protect the non-patrimonial aspects of a person's existence – 'who a person is rather than what a person has'. As the propagation of sexually explicit images of an individual without their consent is clearly an affront to the esteem of that individual, it is argued that instances of revenge porn ought to be considered actionable as iniuria in modern Scottish law.